2023
DOI: 10.1021/acs.analchem.3c02675
|View full text |Cite
|
Sign up to set email alerts
|

Active Tracking of Temporally Changing Gas-Phase Odor Mixture Using an Array of Cells Expressing Olfactory Receptors

Abstract: A cell expressing an olfactory receptor (OR) exhibits excellent odorant detection ability and thus is widely applied in odor biosensors. Most of those biosensors, however, could detect only liquid-phase nonchanging single-component odorants. In this paper, we raised up an odor biosensor for the active tracking of temporally changing gas-phase odor mixture by an array of cells expressing ORs. A thin stable liquid film covered the cell, thus allowing gas-phase odorants to penetrate. The online image processing g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In this study, we showed discrete and continuous odor quantification towards gas-phase odorants. We fixed the cell radius to decrease the noise in image processing, thereby achieving higher quantification resolution than our previous results [21,26]. Single component odor and binary odor mixture were quantified and different target odor stimulation durations were tested to prove the feasibility of these methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we showed discrete and continuous odor quantification towards gas-phase odorants. We fixed the cell radius to decrease the noise in image processing, thereby achieving higher quantification resolution than our previous results [21,26]. Single component odor and binary odor mixture were quantified and different target odor stimulation durations were tested to prove the feasibility of these methods.…”
Section: Discussionmentioning
confidence: 99%
“…This thin liquid film enabled shorter response time for our biosensor [25]. Then we utilized this gas-phase odor biosensor for actively tracking temporally changing odorant [26]. Although so many efforts have been made, the quantification speed was not fast enough and the quantification accuracy was relatively low.…”
Section: Introductionmentioning
confidence: 99%
“…The cells expressing OR has a similar function to OSN. Meanwhile, it can be passaged for many generations with steady characteristics, and the OR types can be freely determined by the researchers [51,52,89,90]. Table 1 lists several examples of cells expressing OR-based odor biosensors.…”
Section: Cell's Expressing Olfactory-receptor-based Odor Biosensormentioning
confidence: 99%
“…(m) Extend lifetime of gas-phase odor biosensor using liquid thickness control and liquid exchange [51]. (n) Actively track temporally changing gas-phase odor mixture [52].…”
Section: Introductionmentioning
confidence: 99%